2000
DOI: 10.1007/bf02679979
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of energy productionin vitro by glutaric acid in cerebral cortex of young rats

Abstract: The present study investigated the effects of glutaric acid (GA), which predominantly accumulates in glutaric acidemia type I (GA-I), on some in vitro parameters of energy metabolism in cerebral cortex of rats. We first evaluated CO2 production from [U-14C] acetate, as well as ATP levels in brain of young Wistar rats. The effect of the acid on the activities of the respiratory chain complexes were also investigated. GA was tested at final concentrations ranging from 0.5 to 5.0 mM. GA significantly reduced brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 22 publications
2
23
1
Order By: Relevance
“…Little is known about cerebrospinal fluid and brain tissue concentrations of GA and its metabolites in GDD patients (1), and there is a complete lack of fetal data. Whereas in most experimental settings described in this article, oligodendrocyte apoptosis was observed with concentrations as little as 0.1 mM, neuronal apoptosis was elicited experimentally using higher concentrations, up to 50 mM (2)(3)(4)17,21,30). Moreover, although experiments have been performed with GA, 3-OH-GA, or GC, all three substances are present within in vivo situations.…”
Section: Discussionmentioning
confidence: 91%
“…Little is known about cerebrospinal fluid and brain tissue concentrations of GA and its metabolites in GDD patients (1), and there is a complete lack of fetal data. Whereas in most experimental settings described in this article, oligodendrocyte apoptosis was observed with concentrations as little as 0.1 mM, neuronal apoptosis was elicited experimentally using higher concentrations, up to 50 mM (2)(3)(4)17,21,30). Moreover, although experiments have been performed with GA, 3-OH-GA, or GC, all three substances are present within in vivo situations.…”
Section: Discussionmentioning
confidence: 91%
“…Previously, we have demonstrated in rat cortex homogenates that GA significantly inhibited in vitro the rate of ATP synthesis, as well as complex I--III activity at 2.5 and 5.0 mM concentrations and complex II--III activity at 5.0 mM GA (37). Therefore, it may be concluded that GA-induced inhibition of energy metabolism in the brain is not specifically directed toward the striatum and probably cannot solely explain the striatal degeneration occurring in GAI patients as recently hypothesized (2).…”
Section: Discussionmentioning
confidence: 98%
“…However, in the last decade alterations of energy metabolism (Ullrich et al 1999;Silva et al 2000;Kö lker et al 2002bKö lker et al , 2004Das et al 2003;Latini et al 2005a;da Costa Ferreira et al 2005a, b;Sauer et al 2005), oxidative stress (de Oliveira Marques et al 2003;Latini et al 2002Latini et al , 2005b and particularly disturbance of the glutamatergic system due to the structural similarity between glutamate, GA and 3-OHGA (Flott-Rahmel et al 1997;Lima et al 1998;Kö lker et al 1999Kö lker et al , 2000aKö lker et al , b, 2002aUllrich et al 1999;Porciú ncula et al 2000Porciú ncula et al , 2004Mello et al 2001;Rosa et al 2004;Frizzo et al 2004) have been considered important pathomechanisms underlying neural damage in GA I. On the other hand, recent works performed on neurons in culture did not confirm excitotoxic actions for 3-OHGA (Lund et al 2004;Freudenberg et al 2004), suggesting that more work is necessary to clarify this matter.…”
Section: Discussionmentioning
confidence: 99%